Optimum Period of Propiconazole Spray for Integrated Management of Wheat Rusts and Karnal Bunt in Punjab - INDU SHARMA; D.J. KAUR; R.C. SHARMA; P.P.S. PANNU (Seed Research, 2026)
Tilt (Propiconazole), a triazole fungicide is applied as a single spray at heading stage to control Karnal bunt (Kb) disease of wheat in Punjab. The present study was undertaken to find out whether this application would also take care of the rusts, which have assumed alarming proportions in the recent past in the state. In order to standardize the appropriate time/stage of fungicidal spray (s) for the combined control of Kb and against stripe rust'and leaf rust of wheat, eleven treatments comprising of single as well double sprays of recommended fungicide, Tilt including a check (unsprayed) were evaluated @ 0.1 per cent for three years (2004-2007) under Punjab conditions at different periods/stages (15th January to 22th March) of the crop. The plots receiving two sprays, respectively, first on 15th February and second on 8th or 22nd March exhibited the maximum disease control of Kb and rusts showing least area under disease progress curve (AUDPC) i.e 396.67 and 455.00, respectively, as compared to 1484.44 in check and maximum economic gains of Rs. 2762.26 and 2304.46/h. Even a single spray applied on 15th February was quite promising showing AUDPC of 734.44 and 89.93 per cent control of Kb with economical gains of Rs. 2042.92.